Evaluation of the implementation of the directly observed treatment strategy for tuberculosis in a large city - Débora Cristina Brasil da Silva Lavôr; Jair dos Santos Pinheiro; Maria Jacirema Ferreira Gonçalves (SciELO, 2016)
Abstract OBJECTIVE To assess the degree of implementation of the Directly Observed Treatment, Short-course - DOTS for tuberculosis (TB) in a large city. METHOD Assessment of the implementation of the logic model, whose new cases of infectious pulmonary TB were recruited from specialized clinics and followed-up in basic health units. The judgment matrix covering the five components of the DOTS strategy were used. RESULTS The result of the logic model indicates DOTS was partially implemented. In external, organizational and implementation contexts, the DOTS strategy was partially implemented; and, the effectiveness was not implemented. CONCLUSION: The partial implementation of the DOTS strategy in the city of Manaus did not reflect in TB control compliance, leading to low effectiveness of the program.